Israel Dulu dan Kini: Sebuah Teologi Biblika Keumatan - Karman, Yonky (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
Chosen people is a term often applied to Jews. However, the post-New Testament church considered Israel’s peoplehood to have ended, a theological assumption that has only been corrected since the mid-20th century. The present article re-examines the concept of the chosen people biblically. The Deuteronomic language for the election of Israel is their deliverance from Egyptian slavery to become a nation of Yahweh’s worshipers (‘ebed peoplehood). However, the Sinaitic Covenant required Israel to be more than that, namely to be a special people, an exemplary peoplehood (segullā peoplehood). The reality of ‘ebed peoplehood is unconditional and its basis is solely the God-factor, His love and fidelity (Deut. 7:6-8). On the contrary, the reality of segullā peoplehood is conditional and its basis is Israel-factor, their seriousness in keeping the covenant (Ex. 19:5-6), which then turned out to fail except for the remnant. However, Israel's failure paved the way for an expanded peoplehood, which includes non-Jews en masse, while the mass salvation of the Jews is an eschatological reality (Rom. 11:25-26).